THEORETICAL AND PRACTICAL FOUNDATIONS OF TEACHING UZBEK FOLKLORE IN PRIMARY GRADES (Journal of Science-Innovative Research in Uzbekistan, 2023)
This scientific article explores the theoretical and practical foundations of incorporating Uzbek folklore into primary grade education. The rich cultural heritage of Uzbekistan is deeply rooted in its folklore, encompassing a diverse array of tales, myths, and traditions that have been passed down through generations. Recognizing the importance of preserving and promoting cultural identity, this article discusses the benefits of integrating Uzbek folklore into primary school curricula. Drawing on educational theories and practical strategies, the article aims to provide insights into creating a comprehensive and engaging framework for teaching Uzbek folklore in primary grades. This comprehensive scientific article examines the theoretical underpinnings and practical methodologies for integrating Uzbek folklore into primary grade education. Uzbekistan, with its rich cultural tapestry, possesses a wealth of folklore that encapsulates the traditions and values of the nation. Recognizing the significance of cultural preservation and educational enrichment, this article explores the potential benefits and challenges of incorporating Uzbek folklore into primary school curricula. Drawing on educational theories, curriculum development strategies, and practical implementation methods, the article provides a holistic framework for educators aiming to introduce Uzbek folklore in primary grades